Nigeria's leadership role in Africa - Wayas, Joseph (London : Macmillan, 1979)
A discourse on African socialism and still growing disequilibrium between Africa and the European economy.
Includes index.
sju 23/01/2019
Loans
Keywords: Nigeria; Africa